2009
DOI: 10.1074/jbc.m809607200
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Analysis of Hrd1p-mediated Retrotranslocation of Its Multispanning Membrane Substrate 3-Hydroxy-3-methylglutaryl (HMG)-CoA Reductase

Abstract: Endoplasmic reticulum (ER)-associated degradation (ERAD)is responsible for the ubiquitin-mediated destruction of both misfolded and normal ER-resident proteins. ERAD substrates must be moved from the ER to the cytoplasm for ubiquitination and proteasomal destruction by a process called retrotranslocation. Many aspects of retrotranslocation are poorly understood, including its generality, the cellular components required, the energetics, and the mechanism of transfer through the ER membrane. To address these qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
104
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(110 citation statements)
references
References 63 publications
(96 reference statements)
6
104
0
Order By: Relevance
“…At endogenous levels of Hrd1, the absence of Hrd3 rendered stable Hrd1 inactive toward all substrates tested. The importance of Hrd3 was also clear at high levels of Hrd1 used to test Hrd1 autonomy in ERAD (17,18). Hrd3 was not required for Hrd1-substrate interaction nor Hrd1 multimerization, but was required for Hrd1-mediated E2-substrate interactions.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…At endogenous levels of Hrd1, the absence of Hrd3 rendered stable Hrd1 inactive toward all substrates tested. The importance of Hrd3 was also clear at high levels of Hrd1 used to test Hrd1 autonomy in ERAD (17,18). Hrd3 was not required for Hrd1-substrate interaction nor Hrd1 multimerization, but was required for Hrd1-mediated E2-substrate interactions.…”
mentioning
confidence: 86%
“…Is Hrd3 simply enhancing the same catalytic process, or is it altering the enzymology of Hrd1? This question is particularly relevant because many studies including our own have capitalized on the dispensability of Hrd3 for examination of Hrd1 in microsomes or reconstituted systems (15,17). Certainly these approaches are useful in studying aspects of the HRD pathway although caution must be exerted in marginalization of Hrd3 in the light of its unveiled importance in Hrd1 action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results complement reports on the dislocation of luminal ERAD substrates (Rodighiero et al, 2002;Elkabetz et al, 2004;Afshar et al, 2005) and of membrane proteins with a single TMs (Huppa and Ploegh, 1997;Tortorella et al, 1998;Ye et al, 2003). Together with recent in vitro evidence for dislocation of ubiquitinated polytopic Ste6*p and Hmg2p (Garza et al, 2009) from yeast microsomes, it seems that, among the possible models suggested for dislocation of polytopic membrane ERAD substrates , complete extraction to the cytosol of intact polypeptide chains is a general feature of the delivery to the proteasome of this class of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, a major difference exists in the mechanism for membrane extraction and cytosolic dislocation of reductase and s: proteolytic activity of proteasomes is required for dislocation of s, whereas reductase dislocation can only be observed upon proteasome inhibition. Proteasome inhibition is known to cause several membrane-bound ERAD substrates in addition to reductase to accumulate in the cytosol of cells (13,(41)(42)(43)(44)(45)(46)(47). It will thus be important to determine in future studies whether membrane extraction and release into the cytosol through sequential actions of VCP/p97 and the proteasome 19 S RP are a general ERAD mechanism or a peculiarity in the sterol-accelerated ERAD of reductase.…”
Section: Discussionmentioning
confidence: 99%